Virtual physical exercise influences on mental health status during COVID-19 outbreak : cross-sectional survey study - Diyana Zulaika Abdul Ghani,; Nguyen, Thuy Van; Zainal Abidin Zainuddin,; Halijah Ibrahim,; Asha Hasnimy Hashim,; Mohd Rustam Rameli, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The severity of Covid-19 outbreak caused it to be declared a pandemic and the Malaysian government had to implement movement control order (MCO). MCO includes restriction on outdoor activities and temporary shutdown of fitness centres. Sports enthusiasts among community may experience uneasy phenomenon as this order affecting their exercises routines. To some extent, it does affect them physically, mentally, and emotionally. Various efforts were made to allow these group to engage in physical exercise. One of the efforts is engaging in live virtual physical exercise (VPE) through social media or recorded videos. Therefore, this study aims to analyse the relationship between VPE and mental health status during COVID-19 pandemic lockdown situation. In this quantitative designed study, 84 participants were recruited randomly within Johor community using snowball effect strategy. DASS-21 questionnaire was used to measure mental health status and administered online for data collection. SPSS software was used for descriptive statistic and SmartPLS software was used to test the structural equation model between the variables. Findings showed significant decreases in the level of stress, anxiety, and depression after joining the VPE programme during MCO. The depression scale was significantly corelated to stress and anxiety before and after involvement with VPE programme. Overall, participants has improved mental health status by engaging with the VPE programme during the lockdown order. This study is expected to shed some light on the future of physical activities via technology and online platform, their influence towards healthy lifestyle and the mental status of the community.